Chemical recycling of poly(cyclohexene carbonate) using a di-MgII catalyst - Singer, FN; Deacy, AC; McGuire, TM; Williams, CK; Buchard, A (Wiley, 2022)
Chemical recycling of polymers to true monomers is pivotal for a circular plastics economy. Here, the first catalyzed chemical recycling of the widely investigated carbon dioxide derived polymer, poly(cyclohexene carbonate), to cyclohexene oxide and carbon dioxide is reported. The reaction requires dinuclear catalysis, with the di-MgII catalyst showing both high monomer selectivity (>98 %) and activity (TOF=150 h−1, 0.33 mol %, 120 °C). The depolymerization occurs via a chain-end catalyzed depolymerization mechanism and DFT calculations indicate the high selectivity arises from Mg-alkoxide catalyzed epoxide extrusion being kinetically favorable compared to cyclic carbonate formation.